Optimizing recovery to support multi-evening cycling competition performance - Richard, N. A.; Koehle, M. S. (European Journal of Sport Science, 2019)
Road criterium and track bicycle racing occur at high speeds, demand repeated high power outputs, last 10-90 min, and offer little chance for recovery after the event. Consecutive evenings of criterium and track racing are respectively known as speed-week or six-day events and take place in evening hours over the course of a week. Given the schedule and timing of these competitions, return to homeostasis can be compromised. No recommendations exist on how to optimize recovery for cyclists participating in these types of repeated evening competitions. Criterium and track cyclists spend considerable time, near and above the individual lactate threshold and therefore mostly utilize carbohydrate as their chief energy substrate. Henceforth, pre- and post-race nutrition and hydration is examined and recommendations are brought forward for carbohydrate, protein, and fluid intake. As evening high-intensity exercise perturbs sleep, strategies to optimize sleep are discussed and recommendations for an optimal sleep environment are given. Active recovery is examined, and the benefits of a short duration low intensity exercise reviewed. Passive recovery methods such as compression garments and cold water immersion are recommended, while evidence for massage, pneumatic compression devices, and neuromuscular electrical stimulation is still lacking. Optimizing recovery strategies will facilitate a return to the resting state following strenuous night competition.